Boy erased [videorecording (DVD)] - Edgerton, Joel, 1974-; Edgerton, Joel, 1974-; Hedges, Lucas, 1996-; Kidman, Nicole, 1967-; Crowe, Russell, 1964-; Conley, Garrard (Universal Pictures Home Entertainment, 2019)
Boy Erased tells the courageous story of Jared Eamons, the son of a Baptist pastor in a small American town, who must overcome the fallout of being outed to his parents. His parents struggle with reconciling their love for their son with their beliefs. Fearing a loss of family, friends, and community, Jared is pressured into attending a conversion therapy program. While there, Jared comes into conflict with its leader and begins his journey to finding his own voice and accepting his true self.